GENDER EQUALITY STUDIES: THE DOMESTIC POLITICAL INFLUENCE ON JAPAN’S OFFICIAL DEVELOPMENT ASSISTANCE (ODA) POLICY (International Conference on Social and Islamic Studies, 2021)
Japan is a country that has concern to gender equality, so that, Japan’s Official Development Assistance (ODA) policy has gender equality values. This paper used domestic political and foreign aid concept and also the power of idea on state policy concept. And then, based on research analysis, so I can conclude that domestic politics, just like, gender equality idea can influence Japan’s ODA policy, so that it can influence Japan’s perspective about distribution of foreign aid to woman development. Gender equality idea can internalize into Japan’s foreign aid policy, so that, it can be applied intorecipients’ countries. But, when Japan distribute ODA foreign aid based on equality gender values to recipient countries, Japan gets some challenges. The challenges are opinion public factor to Prime Minister of Japan, Shinzo Abe. Beside that, also factor of conservative cultural norm and patriarchy system in recipients’ countries which is developing country or poor country.